Managerial characteristics and its impact on organizational performance: evidence from Syria - Milana, Elias; Maldaon, Issa (Business: Theory and Practice, 2015)
This study aims to explore impact of managerial human capital in performance of a Syrian public organization, Directorate of Finance of province of Damascus, through use some of managerial characteristics are age, level of education, tenure and functional track. This study applied on a sample of 12 managers and 138 employees. The study reveals that there are no significant effect of age, level of education and functional track in performance of Directorate of Finance of province of Damascus, while there is a positive, strong and significant effect of tenure manager in organizational performance, which indicates that managerial characteristics almost irrelevant with performance of Directorate of Finance of the province of Damascus, and the public sector in general. Such results appear a need for efforts are invested in the formulation and implementation of human resource procedures and policies which can bring about effective change in behaviours and roles of the public managers and employees.